Comparative Efficacy of Intracoronary Allogeneic Mesenchymal Stem Cells and Cardiosphere-Derived Cells in Swine with Hibernating Myocardium - Weil, Brian R. (Circ Res, 2015)
RATIONALE: Allogeneic bone marrow-derived mesenchymal stem cells (MSCs) and cardiosphere-derived cells (CDCs) have each entered clinical trials but a direct comparison of these cell types has not been performed in a large animal model of hibernating myocardium. OBJECTIVE: Using completely blinded methodology, compare the efficacy of global intracoronary allogeneic MSCs (icMSCs, ~35×10(6)) and CDCs (icCDCs, ~35×10(6)) vs. vehicle in cyclosporine-immunosuppressed swine with a chronic LAD stenosis (n=26). METHODS AND RESULTS: Studies began 3-months after instrumentation when wall-thickening (%WT) was reduced (LAD%WT 38±11% (mean ± SD) vs. 83±26% in remote, p<0.01) and similar among groups. Four-weeks after treatment, LAD%WT increased similarly following icCDCs and icMSCs, while it remained depressed in vehicle-treated controls (icMSCs: 51±13%; icCDCs: 51±17%; vehicle: 34±3%, treatments p<0.05 vs. vehicle). There was no change in myocardial perfusion. Both icMSCs and icCDCs increased LAD myocyte nuclear density (icMSCs: 1601±279 nuclei/mm(2), icCDCs: 1569±294 nuclei/mm(2), vehicle: 973±181 nuclei/mm(2), treatments p<0.05 vs. vehicle) and reduced myocyte diameter (icMSCs: 16.4±1.5 μm, icCDCs: 16.8±1.2 μm, vehicle: 20.2±3.7 μm, treatments p<0.05 vs. vehicle) to the same extent. Similar changes in myocyte nuclear density and diameter were observed in the remote region of cell-treated animals. Cell fate analysis using Y-FISH demonstrated rare cells from sex-mismatched donors. CONCLUSIONS: Allogeneic icMSCs and icCDCs exhibit comparable therapeutic efficacy in a large animal model of hibernating myocardium. Both cell types produced equivalent increases in regional function and stimulated myocyte regeneration in ischemic and remote myocardium. The activation of endogenous myocyte proliferation and regression of myocyte cellular hypertrophy support a common mechanism of cardiac repair.